2021
DOI: 10.1111/cas.14979
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microbiota contributes to predicting the response to immune checkpoint inhibitors in non‐small‐cell lung cancer patients

Abstract: Immunotherapy against cancer, through immune checkpoint inhibitors targeting the programmed cell death‐1/programmed cell death‐ligand 1 axis, is particularly successful in tumors by relieving the immune escape. However, interindividual responses to immunotherapy are often heterogeneous. Therefore, it is essential to screen out predictive tumor biomarkers. In this study, we analyzed the commensal microbiota in stool samples and paired sputum samples from 75 metastatic non‐small‐cell lung cancer (NSCLC) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 40 publications
2
43
1
Order By: Relevance
“…Zhang et al. ( 134 ) found that featured respiratory microbes such as enriched Streptococcus may enhance antitumor immune responses by increasing antigen presentation and effector T cell function, which may increase the incidence of irAEs, including CIP.…”
Section: Mechanisms Of Pd-1/pd-l1 Inhibitor-induced Pulmonary Toxicitymentioning
confidence: 99%
“…Zhang et al. ( 134 ) found that featured respiratory microbes such as enriched Streptococcus may enhance antitumor immune responses by increasing antigen presentation and effector T cell function, which may increase the incidence of irAEs, including CIP.…”
Section: Mechanisms Of Pd-1/pd-l1 Inhibitor-induced Pulmonary Toxicitymentioning
confidence: 99%
“…Recent studies have demonstrated that gut microbiome is associated with NSCLC progression. Patients with higher gut microbiota alpha diversity ( Zhang C. et al., 2021 ), and those enriched in some microbes, such as Phascolarctobacterium ( Zhang F. et al., 2021 ), Ruminococcaceae UCG 13 , and Agathobacter ( Hakozaki et al., 2020 ), were found to have better PFS. In the current study, we found that the long-PFS group had the highest F/B value and significantly higher diversity in Fungi, Archaea, and Viruses among three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, recent evidence has demonstrates that gut dysbiosis might impair the systemic response to efficacy in advanced cancer patients. Studies have documented that it is possible to predict based upon their gut microbiome whether the cancer patients are hyper-responder or non-responder to immune checkpoint inhibitor-based immunotherapy [ 86 ]. The alpha diversity between the gut and respiratory microbiota was not linked, and only the gut microbiota alpha diversity was associated with anti-programmed cell death-1 response.…”
Section: The Lung Microbiome During Diseasementioning
confidence: 99%
“…The alpha diversity between the gut and respiratory microbiota was not linked, and only the gut microbiota alpha diversity was associated with anti-programmed cell death-1 response. Higher gut microbiota alpha diversity indicated better response and more prolonged progression-free survival [ 86 ]. Antitumor immunotherapy is promising, however, very costly, leading to an increase in the social-economic burden.…”
Section: The Lung Microbiome During Diseasementioning
confidence: 99%